The Mediating Effects of Brand Preference to Customer Satisfaction - Agus Zainul Arifin, Jasin Mochammad, Dytta Novrianda, Pudji Astuti, Christina Catur Widayati, (Jurnal Manajemen, 2018)
The purpose of this study is to analyze the influence ofÃ‚Â  brand preference to customer satisfaction (advertiser). Samples consists of one hundred andÃ‚Â  twenty persons of decision makers of government advertisemen programs in various government agencies and state owned companies. Data was collected by using self-completed questionnaire. Structural Equation Modelling used to analyze the indicator variables, latent variables and measurement error variables Ã‚Â to determine of causal brand awareness, brand association, brand extension, perceived quality to customer satisfaction throughÃ‚Â  brand preference of Sindo Media (MNC Group). The finding reveals a significant influence on mediated variables. While Brand awareness, Brand association, Brand extension, Perceived quality, has a significant influence on customer satisfaction. That means Brand preference has significant influence to customer satisfaction.Ã‚Â Ã‚Â Ã‚Â